83.8k views
15 votes
HelP me please ASAP please 15 points

SOLVE #1 BY ELIMINATION AND #2 BY SUBSTITUTICATED
1. x - 2y = 14

x + 3y = 9


2. y = 2x

5x - y = 9

User Randal
by
6.1k points

1 Answer

9 votes

Answer:

Explanation:

x - 2y = 14

x + 3y = 9

subtract the first equation from the second to eliminate the x terms:

x + 3y = 9

-x + 2y = -14

-----------------

5y = -5

y = -1

x - 2(-1) = 14

x = 12

:::::

y = 2x

5x - y = 9

Substitute 2x for y in the second equation?:

5x - 2x = 9

3x = 9

x = 3

y = 6

User Wojteq
by
6.2k points